A database of landslides triggered by 2014 Mw 6.1 Jinggu earthquake, China. Issue 5 (October 2021) - He, Xiangli; Xu, Chong; Qi, Wenwen; Huang, Yuandong; Chen, Yu; Wen, Boyu
Abstract: On October 7, 2014, a Ms 6.6 earthquake occurred in Jinggu County, Yunnan Province, China, causing some casualties and property damage. A database of landslides was created based on high-resolution satellite images taken before and after the earthquake. The results show that this event triggered at least 441 coseismic landslides, with a total area of 1.08 km 2, distributed in the VII-VIII intensity zone, with an area of about 2160.86 km 2 . The total volume of these landslides is estimated to be 9.4×10 6 m 3 according to the area-volume formula. The point density, area percentage, and volume density of the landslides in the study area are 0.20 km −2, 0.05%, and 0.004 m, respectively. The comprehensive results show that the Jinggu earthquake landslides are mostly relatively small-scale and develop in a wide range. We consider the influence of topographic factors and river systems on coseismic landslide distribution using landslide number density (LND) and land area percentage (LAP). It indicated that LND and LAP generally increase as the elevation and distance to watershed decrease and slope angle increases and are relatively larger in southeast-facing and concave slopes. This detailed coseismic landslide database for the Jinggu earthquake is essential for the subsequent regional risk assessment.